The Role of Prophetic Leadership on Workplace Spirituality At sufism-based Islamic Boarding School - Hamidah; Mahmuddin Yasin; irfan budiono (Journal of Business and Behavioural Entrepreneurship, 2020)
The purpose of this study is to analyze the effect of prophetic leadership on the workplace spirituality among officials and employees in an Islamic boarding school. This quantitative research used data collection through a survey, in a form of a set of questionnaire, in the Sufism-based Islamic boarding school in Tasikmalaya, Indonesia. The study sample consisted of 270 officials and employees of the boarding school. The data was analyzed using SEM with the AMOS 24 program, to test the effects. The research findings showed a significant effect of the prophetic leadership on the workplace spirituality. Originality of this research lies on the unit analysis of officials and employees at the sufism-base Islamic boarding school